Ethical Encounters through Travelling Images - Mitchell, Claudia (Art/Research International)

(untitled) (University of Alberta, 2025)
This article brings together two broad areas in arts-based research: curation and the study of how images travel. At the centre of this work is a concern for what might be described as “ethical encounters”, drawing on an autoethnographic project working with family photographs, reenactments, and travel from Canada to the U.K. as the “Old Country”. Questions about who is in the picture and what is said and not said about a family photograph arise about what can be shown, and about stories of what is left out. But this work with family photos and travel does not sit alone; rather, it gives rise to questions about curating participant-generated images in community-based research, including the drawings of war-affected children and photos on gender transformation produced in a variety of Global South contexts. The article concludes with the idea that the concept of travelling offers opportunities to challenge normative, colonial, and hegemonic ideas; maybe even advancing social change.